Experimental and Theoretical Studies on the Rearrangement of 2‐Oxoazepane α, α‐Amino Acids into 2′‐Oxopiperidine β2, 3, 3‐Amino Acids: An Example of Intramolecular Catalysis. Issue 6 (17th December 2014) - Núñez‐Villanueva, Diego; Bonache, M. Ángeles; Lozano, Laura; Infantes, Lourdes; Elguero, José; Alkorta, Ibon; García‐López, M. Teresa; González‐Muñiz, Rosario; Martín‐Martínez, Mercedes
Abstract Enantiopure β‐amino acids represent interesting scaffolds for peptidomimetics, foldamers and bioactive compounds. However, the synthesis of highly substituted analogues is still a major challenge. Herein, we describe the spontaneous rearrangement of 4‐carboxy‐2‐oxoazepane α, α‐amino acids to lead to 2′‐oxopiperidine‐containing β2, 3, 3‐amino acids, upon basic or acid hydrolysis of the 2‐oxoazepane α, α‐amino acid ester. Under acidic conditions, a totally stereoselective synthetic route has been developed. The reordering process involved the spontaneous breakdown of an amide bond, which typically requires strong conditions, and the formation of a new bond leading to the six‐membered heterocycle. A quantum mechanical study was carried out to obtain insight into the remarkable ease of this rearrangement, which occurs at room temperature, either in solution or upon storage of the 4‐carboxylic acid substituted 2‐oxoazepane derivatives. This theoretical study suggests that the rearrangement process occurs through a concerted mechanism, in which the energy of the transition states can be lowered by the participation of a catalytic water molecule. Interestingly, it also suggested a role for the carboxylic acid at position 4 of the 2‐oxoazepane ring, which facilitates this rearrangement, participating directly in the intramolecular catalysis.